Having comes from saving - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Manual for Preservation of Food and Condiments in the Home. V Figueroa and J Lama. Community Project: Preservation of Food. 1999. 106 pp. ISBN 959 7098 08 3 US$6 6 (only orders in larger quantities from institutions can be accepted. Price is exclud